2018
DOI: 10.1155/2018/4718428
|View full text |Cite
|
Sign up to set email alerts
|

A Chronic Glottic Foreign Body Diagnosed by Radiograph after 9 Months of Symptoms

Abstract: A six-year-old girl presented to an emergency room after describing choking on a rubber band. She was in no distress and was discharged. Over the course of the next 9 months, she had numerous outpatient and emergency room visits due to intermittent stridor, difficulty breathing, and hoarseness. Eventually, dedicated airway films revealed a laryngeal foreign body. During rigid bronchoscopy, a two-centimeter rubber band was discovered in the larynx. It extended from the supraglottis, through the glottis, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…This led to a DLB being performed, where it was discovered that the patient had aspirated small paper fragments [17]. Rosenthal et al reported a case of a six-year-old girl with intermittent stridor, difficulty breathing, and hoarseness for nine months due to an embedded laryngeal foreign body [18].…”
Section: Discussionmentioning
confidence: 99%
“…This led to a DLB being performed, where it was discovered that the patient had aspirated small paper fragments [17]. Rosenthal et al reported a case of a six-year-old girl with intermittent stridor, difficulty breathing, and hoarseness for nine months due to an embedded laryngeal foreign body [18].…”
Section: Discussionmentioning
confidence: 99%
“…A flexible fibre optic laryngoscopy (FFL) was performed through her nose as the likelihood of a foreign body aspiration increased. Using a bronchoscope, a visible loop of rubber band was removed from the supraglottis [ 10 ]. Previous cases describe the variety of how foreign body aspiration can present with symptoms or asymptomatic, which makes establishing the diagnosis a little difficult.…”
Section: Discussionmentioning
confidence: 99%